Construction and Transformation of OsERA1 Gene into Expression Vector and Response of Nipponbare-OsERA1 Transgenic Rice to Drought Stress - Tri Joko Santoso; Aniversari Apriana Apriana; Atmitri Sisharmini Sisharmini; Kurniawan Rudi Trijatmiko (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2018)
Drought stress is a major constrain which could influence rice productivity. Enhanced Response to ABA1 (ERA1) gene encoding a β-subunit farnesyltransferase enzyme plays a role to control sensitivity of the guard cells to abscisic acid (ABA), hence regulating drought stress response in plant species including rice. This study aimed to clone the OsERA1 gene into expression vector, introduce it into rice plant, and confirm the positive OsERA1-rice plants conferring drought tolerance. This study was initiated by isolation of the OsERA1 gene from rice cDNAs and cloned it to an expression vector cassette, pCAMBIA1301. The cassette harboring OsERA1 gene was introduced into rice plant cv. Nipponbare mediated by Agrobacterium tumefaciens strain LBA4404.Putative transgenic lines were detected using PCR and Southern blot analyses to confirm the inserted transgene and the positive lines were assayed their tolerance to drought. The OsERA1 gene was successfully isolated and constructed into expression vector to generate pCAMBIA1301-OsERA1. Introduction of the gene into Nipponbare has produced nine putative transgenic rice lines, of which, six lines harbored OsERA1 gene. Southern blot analysis of sixteen T2 plants from two PCR-positive transgenic lines revealed1–3 copies of transgene were integrated into rice genome of transgenic lines. Five transgenic lines of Nipponbare-OsERA1 showed better response to drought at vegetative phase compared to control in term of recovery ability. At generative phase, the five transgenic lines yielded less unfilled grains compared to control. Overall, the transgenic lines obtained from this study could bepotential candidates for developing rice varieties tolerant to drought.